2010
DOI: 10.1080/20786204.2010.10874048
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes, perceptions and understanding amongst teenagers regarding teenage pregnancy, sexuality and contraception in Taung

Abstract: 2 Declaration I, the undersigned, hereby declare that the work contained in this thesis is my own work and that I have not previously submitted it to any other university for degree purpose. Signature: ___________________ Dr Kanku3 Abstract Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 40 publications
5
44
0
2
Order By: Relevance
“…It was posited that adolescents in Nigeria have a high burden of reproductive health problems (Ahonsi, 2013). This assertion is supported by earlier surveys conducted on sexual behaviours of Nigerian Adolescents (National Demographic Health Survey, 2008; Federal Ministry of Health, 2011) which indicated that Nigerian adolescent (15)(16)(17)(18)(19) almost half of the females (46.2%) and about a quarter of males (22.1%) have engaged in sexual intercourse.…”
Section: Introductionmentioning
confidence: 61%
“…It was posited that adolescents in Nigeria have a high burden of reproductive health problems (Ahonsi, 2013). This assertion is supported by earlier surveys conducted on sexual behaviours of Nigerian Adolescents (National Demographic Health Survey, 2008; Federal Ministry of Health, 2011) which indicated that Nigerian adolescent (15)(16)(17)(18)(19) almost half of the females (46.2%) and about a quarter of males (22.1%) have engaged in sexual intercourse.…”
Section: Introductionmentioning
confidence: 61%
“…These results are supported by a study in Australia, [5] which revealed adolescents who accept and continue with their pregnancy perceive adolescent parenting as a positive and transformative experience that influenced personal growth. Similarly, a qualitative study in South Africa, [14] found that many adolescents perceived benefits from pregnancy, such as proof of one's fertility, increased revenue from older men, enjoyment of sex, believing they would get a grant, and possibly benefit from a second pregnancy. The study also revealed the negative aspects of adolescent pregnancy, such as pregnancy complications, infertility from termination, STI risks including HIV, increased burden of babysitting, and loss of education and employment.…”
Section: Association Between Sociodemographic Variables and Perceptionsmentioning
confidence: 99%
“…[5] In contrast, adolescents in South Africa believed their future would be negatively affected as parents separating and blaming each other. [14] In SSA, adolescents face many challenges that affect their perceptions and their health. Rwandan adolescents face many barriers, such as access to healthcare and literacy, due to medical standards and legal issues that considers them too old for pediatric services, yet too young to make their own decisions with preventive care and treatment.…”
Section: Perceptions Of Adolescent Parentingmentioning
confidence: 99%
See 1 more Smart Citation
“…Teenage pregnancy is a public health concern (Chanjar, Chommanard and Lookid, 2009;Richter andMlambo, 2005) as most teenage pregnancies fall in the category of high risk pregnancies which require appropriate care during the antenatal, labour and postnatal periods to ensure good health for the mother and child (Nolte, 2011;Restrepo-Méndez, Barros, Santos, Menezes,Matijasevich,Barros and Victoria, 2011;Ehlers, 2010;James, van Rooyen and Strumpher, 2010;Kanku and Mash, 2010). According to Chopra, Daviaud, Pattinson, Fonn and Lawn (2009), regular antenatal visits and improved referral links between the home and the health facility are required to reduce child mortality and improve maternal health in South Africa.…”
Section: Introductionmentioning
confidence: 99%